The influence of behavioural factors on choice of unit trust fund among retail investors in Malaysia. - Tan Boon Pin (2018)
This study investigates whether behavioural factors influencing the choice of fund among retail investors in Malaysia, by using mixed methods. There are not many studies done on unit trust fund and most of it focus on performance and comparative studies between conventional and sharia by using quantitative methods. The present study used three new independent variables and a new dependent variable and integrates Prospect Theory into the framework, which had not been tested in unit trust fund investment. Adapted questionnaire of five pages was prepared in dual language (English and Bahasa Malaysia) to collect data. The samples were drawn from four states, namely Kelantan, Terengganu, Penang and Kuala Lumpur through the unit trust consultants, friends and relatives who have invested in the unit trust fund. After screening, a total of 333 questionnaires were deemed completed and usable. Participation was voluntary. A pilot test was carried out for both quantitative and qualitative studies in Kelantan, and minor changes to the questionnaires were made according to the feedback from the respondents. The descriptive statistics, Pearson moment product correlation, partial correlation and multiple regression were used to analyse the quantitative survey where thematic and pattern-based analysis was carried out for the qualitative survey. The five hypotheses were found to be statistically significant. On the qualitative study, eight questions based on the five hypotheses were derived to explain and provide a deeper insight into the quantitative findings. Face to face semi-structured interview was carried out with twelve respondents with more than five years of experience. The study was carried out concurrently. The qualitative findings were able to reaffirm and explain the quantitative findings, and three new themes were discovered. The findings were merged into a side by side comparison table. A diagrammatic Grounded theory lite was produced. It depicts heuristic as an independent variable while considering the past, financial knowledge and miscalibration as a dimension. Relationship and trust is the moderator, while herding as mediator. It was validated by respondents who are experts with more than five years of experience in unit trust fund investment, theoretical saturation, analysis of verbatim and citations. The findings showed that the retail investors were considering the past and financial knowledge to choose their fund. It was discovered that retail investors were influenced by behavioural factors and considering the past and financial were the main factors that caused it. Following that, a conceptual model was conceptualised. The implication was that Prospect Theory was able to provide a better explanation than the standard traditional utility theory under the risky situation. The mixed method triangulation design was able to provide a more precise answer to the research questions and to the retail investors it had to be more careful as it was discovered that behavioural factors influenced the choice of fund. It is highly recommended that further study be conducted by using other behavioural factors and respondents from other states.